2012
DOI: 10.1111/j.1540-8175.2012.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Conventional and Tissue Doppler Echocardiography in the Noninvasive Measurement of Right Atrial Pressure

Abstract: Of all echocardiographic variables investigated, tricuspid annular E/E' ratio is identified as the best index for noninvasive determination of RAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
1
21
2
Order By: Relevance
“…Although TR jet maximum velocities were similar in two groups, RAP TTE and delta RAP were significantly higher in group 2. 19 New echocardiographic formulas using these parameters and other possible parameters should be created and tested in further studies. 3,12,13 However, the association between the RAP overestimation and severe TR was not analyzed in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although TR jet maximum velocities were similar in two groups, RAP TTE and delta RAP were significantly higher in group 2. 19 New echocardiographic formulas using these parameters and other possible parameters should be created and tested in further studies. 3,12,13 However, the association between the RAP overestimation and severe TR was not analyzed in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the ability of echocardiographic parameters to assess mean RAP in patients with various cardiac disorders. 11,12,[15][16][17][18] Inspection of the IVC with measurement of the diameter and the effect of breathing or sniffing (collapsibility) is the method that is most thoroughly studied, 11,12,[15][16][17] and has gained the most widespread use. In this study, we found a high degree of concordance between right-and left-sided filling pressures in HTx recipients.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 The mitral and tricuspid E/e′ ratio was calculated and considered as a reliable index of LA and RA filling pressures. 24,[26][27][28] Speckle-Tracking Echocardiography of RA and LA Two-dimensional (2D) speckle-tracking echocardiography was obtained and recorded using conventional 2D gray-scale echocardiography during breath holding with stable electrocardiographic tracing, as described previously for LA and RA. 9,29,30 Offline analysis was performed using a commercially available semiautomated 2D strain software (EchoPAC PC, version 112, rev.…”
Section: Standard and Tissue Doppler Imagingmentioning
confidence: 99%